2015
DOI: 10.1590/1983-084x/14_012
|View full text |Cite
|
Sign up to set email alerts
|

Análise fitoquímica e atividade fotoprotetora de extrato etanólico de Euphorbia tirucalli Linneau (Euphorbiaceae)

Abstract: Palavras-chave: Euphorbia tirucalli Linneau, avelós, atividade fotoprotetora A B S T R A C T: P h y t o c h e m i c a l a n a l y s i s a n d p h o t o p r o t e c t i v e a c t i v i t y o f theethanolic extract of Euphorbia tirucalli Linneau (Euphorbiaceae).Euphorbia tirucalli Linneau, popularly known as "avelos", "naked cock" or "naked dog", is used in popular medicinein order to treat cancer, antibiotic and antiviral diseases. Herbal medicines are often employed in order to assist or replace conventional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
0
8
0
7
Order By: Relevance
“…J. multifida has been popularly used to treat various conditions, such as fever, pain, infection, wounds, ulcers and various infectious skin diseases (38) . Thus, several studies have focused on the biological properties of the plant, and initial research shows that this plant species has shown antioxidant, antibacterial, antiinflammatory, antifungal, gastroprotective, healing, analgesic, immunomodulatory activity, among others (39) .…”
Section: Medicinal Usementioning
confidence: 99%
See 1 more Smart Citation
“…J. multifida has been popularly used to treat various conditions, such as fever, pain, infection, wounds, ulcers and various infectious skin diseases (38) . Thus, several studies have focused on the biological properties of the plant, and initial research shows that this plant species has shown antioxidant, antibacterial, antiinflammatory, antifungal, gastroprotective, healing, analgesic, immunomodulatory activity, among others (39) .…”
Section: Medicinal Usementioning
confidence: 99%
“…These results suggest that the featured plant may have potent skin lightening ingredients, which corroborates other studies that address the photoprotective power developed by several plant species. The result of a research entitled "Análise fitoquímica e atividade fotoprotetora de extrato etanólico de Euphorbia tirucalli L. (Euphorbiaceae)", belonging to the same family as Jatropha, suggests that its ethanol extract has a possible photoprotective effect (38) .…”
Section: Anti-melanin Deposition Activitymentioning
confidence: 99%
“…As plantas representam um importante banco de moléculas fitoquímicas de grande importância para o homem, a fotoproteção apresenta vários estudos com extratos vegetais, visto que, devido a sua composição fitoquímica formam uma camada protetora sobre a derme prevenindo as queimaduras causadas pelas fontes de radiação ultravioleta. As fontes UV, são deletérias para as células, causando a nível celular o desenvolvimento de cânceres como melanoma e o envelhecimento precose Vale, 2015;Vieira e Orlanda, 2018).…”
Section: Eluentesunclassified
“…According to Saewan and coauthors [69], the presence of phenolic compounds in photoprotective emulsions take a prominent position in terms of the spectral absorption of the solar radiation in the UVB range with antiaging and photoprotection purposes [70]. The Mansur method, used to determine the sun protection factor (SPF), resulted the photoprotective activity of the pequi oil present in the formulation.…”
Section: Pequi Oil Cream Sun Protection Factor (Spf)mentioning
confidence: 99%